Answer:
(A)
![\Delta H^(\circ )_(r)= -144 kJ](https://img.qammunity.org/2020/formulas/chemistry/college/eal2zqb9jpmw3nocwwmldx5slao6fg5lcr.png)
(B)
![\Delta H^(\circ )_(r)= - 2552kJ](https://img.qammunity.org/2020/formulas/chemistry/college/b3g7wth6hxw3ljqgi1syp3ao4o898ilucp.png)
Step-by-step explanation:
(A) 2NO(g) + O₂(g) → 2NO₂(g)
![1/2 N_(2)(g)+O_(2)(g)\rightarrow NO_(2)(g), \Delta H^(\circ )_(a)=33.2 kJ....equation (a)](https://img.qammunity.org/2020/formulas/chemistry/college/ubznrh42pwa4b8xyi60qrsneugfnkfhpgd.png)
Now, multiplying equation (a) with 2:
⇒
![N_(2)(g)+2 O_(2)(g)\rightarrow 2 NO_(2)(g)....equation (a)](https://img.qammunity.org/2020/formulas/chemistry/college/e1u781ktq2zasbwwkuozkeesz6qtvpsbga.png)
Then equation b is reversed and multiplied with 2:
![2 NO(g)\rightarrow N_(2)(g)+ O_(2)(g)....equation (b)](https://img.qammunity.org/2020/formulas/chemistry/college/a6hrcsg7q3x6z1pjwf52nwxl1doqpg7nx6.png)
Now by adding the equation (a) and equation (b), we get:
⇒
![2 NO(g)+ \bcancel N_(2)(g)+\bcancel 2 O_(2)(g)\rightarrow 2 NO_(2)(g) +\bcancel N_(2)(g)+ \bcancel O_(2)(g)](https://img.qammunity.org/2020/formulas/chemistry/college/sxbtnp04ntyr0ls3e21km3o8pbb5hnxvv4.png)
⇒ 2NO(g) + O₂(g) → 2NO₂(g)
Therefore, the enthalpy of the reaction:
![\Delta H^(\circ )_(r)= 2* \Delta H^(\circ )_(a) - 2* \Delta H^(\circ )_(b)](https://img.qammunity.org/2020/formulas/chemistry/college/zb5ew2hu1rrerym85w513zpzodz3h3wwon.png)
![= (2*33.2)- (2*90.2)=66.4 - 180.4= -144 kJ](https://img.qammunity.org/2020/formulas/chemistry/college/qsj5uajzck93ceewpi3yao4kvtsjctewn1.png)
(B) 4B(s)+3O₂(g) → 2B₂O₃(s)
![B_(2)O_(3)(s)+3H_(2)O(g)\rightarrow 3O_(2)(g)+B_(2)H_(6)(g), \Delta H_(a )^(\circ )=+2035 kJ...equation (a)](https://img.qammunity.org/2020/formulas/chemistry/college/j42j9qsvojkc2crd3xzw4e25288dz412tc.png)
![2B(s)+3H_(2)(g)\rightarrow B_(2)H_(6)(g), \Delta H_(b )^(\circ )= +36 kJ...equation (b)](https://img.qammunity.org/2020/formulas/chemistry/college/bl2kjekkms1vs4zb6ijwxbg4q12y7frsrq.png)
![H_(2)(g)+1/2O_(2)(g)\rightarrow H_(2)O(l), \Delta H_(c )^(\circ )= -285 kJ...equation (c)](https://img.qammunity.org/2020/formulas/chemistry/college/6gocdgbd1xiw965tjepza9n5v7nib1cu5o.png)
![H_(2)O(l)\rightarrow H_(2)O(g), \Delta H_(d )^(\circ )=+44 kJ...equation (d)](https://img.qammunity.org/2020/formulas/chemistry/college/u4kjsqitnoqx3oem7wsr32m72bx2x7mshb.png)
Now multiplying equation (b) with 2, reversing equation (a) and multiplying with 2. Reversing equation (c) and (d) and multiplying both with 6.
![4B(s)+6H_(2)(g)\rightarrow 2B_(2)H_(6)(g)...equation (b)](https://img.qammunity.org/2020/formulas/chemistry/college/k1scbewj3gligmu1pg7gsmoy8vjsmoto6x.png)
![6H_(2)O(l)\rightarrow 6H_(2)(g)+3O_(2)(g)...equation (c)](https://img.qammunity.org/2020/formulas/chemistry/college/dp5n1dy8y72yzf3f1r4nax32si24xnzn3c.png)
![6H_(2)O(g)\rightarrow 6H_(2)O(l)...equation (d)](https://img.qammunity.org/2020/formulas/chemistry/college/1la8g9ckspzk86wy0hwwe39soi6r8k7mjm.png)
Now by adding the equations (a), (b), (c), (d); we get:
4B(s)+3O₂(g) → 2B₂O₃(s)
Therefore, the enthalpy of the reaction:
![\Delta H^(\circ )_(r)= -2* \Delta H^(\circ )_(a) + 2* \Delta H^(\circ )_(b) - 6 * \Delta H_(c )^(\circ ) - 6 * \Delta H_(d )^(\circ )](https://img.qammunity.org/2020/formulas/chemistry/college/8i8kdzrl516qrllnixihxw5k4vayqvcvx0.png)
![= -2* (+2035 kJ)+ 2* (+36 kJ) - 6 * (-285 kJ)- 6 * (+44 kJ) = -4070 + 72 + 1710 - 264 = - 2552kJ](https://img.qammunity.org/2020/formulas/chemistry/college/qp33iosdd8a4jdoima7dk5ct57n578v5in.png)